Theory and practice of model transformations 4th international conference, ICMT 2011, Zurich, Switzerland, June 27-28, 2011. Proceedings - Cabot, Jordi; Visser, Eelco (Lecture Notes in Computer Science, 2011)
This book constitutes the refereed proceedings of the 4th International Conference, ICMT 2011, held in Zurich, Switzerland in June 2011. The 14 revised full papers were carefully revised and selected from 51 submissions. The scope of the contributions ranges from theoretical and methodological topics to implementation issues and applications. Topics addressed are such as transformation paradigms and languages, transformation algorithms and strategies, implementation and tools, as well as applications and case studies.